DETERMINAN PEMILIHAN KONTRASEPSI PADA PASANGAN USIA SUBUR SEBAGAI UPAYA MENEKAN BABY BOOMS DI MASA PANDEMIC COVID-19 DI DESA WARU PARUNG BOGOR - Hasanah, Uswatun; Hakim, Amelia Nurul; Annisa, Mega (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2023)
ABSTRACTCouples of childbearing age ranging in age from 20-45 years where the couple (male and female) is mature enough in all matters especially in the reproductive organs are already functioning properly. Contraception is derived from the word